South African Teachers Caught Between Nation Building and Global Demands: Is There a Way Out/Forward?. Issue 4 (3rd July 2016) - Bantwini, Bongani D.; Letseka, Moeketsi
Abstract : In this article, we explore the impact of the nation-building and global demands on teachers' work and how they survive the pressure of, and reconcile, these various demands that impact their work. We draw on two separate data sets that emerged from studies undertaken in the Eastern Cape Province (EC), South Africa. Findings reveal a rift between the nation-building and global mandates. Most intended changes assumed that teachers are ready and prepared for whatever changes that are introduced. Consequently, teachers are in a constant struggle to come to terms with them, thus resulting in slow implementation or the nonimplementation of reforms in classrooms. We argue that recognition and acknowledgment of existing realities, classroom cultures, and implementation requirements or support should be the first step in improving education. Also, a strong visionary leadership becomes pivotal to achieve the desired reform success. Additionally, policy development and programs need to recognize the country's history and the murky terrain that still has to be navigated to ensure successful curriculum reform implementation.